Mapping the landscape of biliary tract cancer in Europe: challenges and controversies - Rimassa, Lorenza; Khan, Shahid; Groot Koerkamp, Bas; Rössler, Stephanie; Andersen, Jesper B.; Raggi, Chiara; Lleo, Ana; Nault, Jean-Charles; Calderaro, Julien; Gabbi, Chiara; Kather, Jakob Nikolas; Banales, Jesus M.; et al. (The lancet. Regional health, 2025)
Biliary tract cancer (BTC) is becoming more common worldwide, with geographic differences in incidence and risk factors. In Europe, BTC may be associated with primary sclerosing cholangitis, lithiasis, and liver cirrhosis, but is more frequently observed as a sporadic disease. BTC increasingly affects patients under 60 years, resulting in a significant social and economic burden. Early diagnosis remains challenging due to vague symptoms in 50% of patients with BTC, and lack of specific biomarkers, resulting in late presentation and poor prognosis. The identification of patients at increased risk and reliable biomarkers require collaborative efforts to make faster progress. This Series paper highlights the disparities in access to diagnostic tools and multidisciplinary care in Europe, particularly in economically disadvantaged regions, while identifying priority areas for improvement. Addressing these inequities requires harmonised guidelines, accelerated pathways to curative treatments, and improved awareness among healthcare professionals and the public. Multidisciplinary teams (MDTs) are crucial for the diagnosis of BTC and for improving patient outcomes, yet inconsistencies exist in their implementation not only between different countries, but also between different centres within a country. Collaboration and standardisation of diagnostic and treatment protocols across Europe are essential to effectively address the management of patients with BTC.